Genetic variation in Fusarium moniliforme isolates from seeds of different crop species - Tripathi, A.N.; Aggarwal, P.C.; khetarpal, R.K.; Bhat, K.V.; Vishunavat, Karuna; Singh, U.S. (Indian Phytopathology, 2011)
PCR based RAPD markers were used for the study of DNA polymorphism among 30 isolates of Fusarium moniliforme isolated from seeds of 12 different crops namely maize, cotton, groundnut, paddy, wheat, barley, sorghum, cowpea, soybean, pigeon pea, okra and chilli. A total of 43, out of 64 RAPD primers screened were selected for genetic variability study. Amplification of genomic DNA of 30 isolates, yielded 314 fragments that could be scored, out of which only one band was monomorphic (OPB-1), with an average of 7.2 polymorphic fragments per primer. Number of amplified fragments ranged from 3 to 15 and varied in size from 100 bp to 3000 bp. Average percentage of polymorphism was 99.42%. The cophenetic correlation between two matrices gave r = 0.916, showing very good fit correlation for a cluster analysis. The similarity coefficient ranged from 0.109 to 0.694. Based on DNA fingerprints, 30 isolates were categorized into two clusters. Isolate FmE2 and FmE3 showed highest degree of similarity (69.4%) with each other. Most of the primers could not differentiate isolates from the same host species, but generated polymorphic bands with isolates from different host species. A number of primers yielded polymorphic bands within isolates from the same hosts. All isolates produced a monomorphic common band of 400 bp with the primer OPB1, which may useful for developing strain specific SCAR marker for identification of F. moniliforme isolates.